2020
DOI: 10.7150/thno.45985
|View full text |Cite
|
Sign up to set email alerts
|

CT quantification of pneumonia lesions in early days predicts progression to severe illness in a cohort of COVID-19 patients

Abstract: Rationale: Some patients with coronavirus disease 2019 (COVID-19) rapidly develop respiratory failure or even die, underscoring the need for early identification of patients at elevated risk of severe illness. This study aims to quantify pneumonia lesions by computed tomography (CT) in the early days to predict progression to severe illness in a cohort of COVID-19 patients. Methods: This retrospective cohort study included confirmed COVID-19 patients. Three quantitative CT features of pneumonia lesions were au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
193
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(208 citation statements)
references
References 26 publications
4
193
0
7
Order By: Relevance
“…First, this was a single-center study, and the results require verification through a multicenter study. Second, the CT scores of this study may not be comparable with the quantitative scores determined using artificial intelligence [33], although visual scores are easier to determine. Finally, only patients with mild COVID-19 pneumonia were included, and the longitudinal CT performance of severe pneumonia must be determined using a larger sample size.…”
Section: Discussionmentioning
confidence: 82%
“…First, this was a single-center study, and the results require verification through a multicenter study. Second, the CT scores of this study may not be comparable with the quantitative scores determined using artificial intelligence [33], although visual scores are easier to determine. Finally, only patients with mild COVID-19 pneumonia were included, and the longitudinal CT performance of severe pneumonia must be determined using a larger sample size.…”
Section: Discussionmentioning
confidence: 82%
“…The %HAA − 700, %HAA − 700–250, and %HAA − 250 showed the highest correlation with overall pneumonia, the sum of ground-glass opacity and crazy-paving pattern, and consolidation extent, respectively. Similar density thresholds were used by Liu et al, who demonstrated that CT features extensions were significant predictors of progression to severe illness in COVID-19 pneumonia [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of CT led to understanding that visual quantification of COVID-19 pneumonia extent and several features (predominant crazy-paving pattern or presence of consolidations) at chest CT are associated with increased risk of death [ 4 – 6 ]. In addition, CT quantitative parameters obtained by software predict the severity of COVID-19 pneumonia and its progression [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other coronavirus pneumonia, COVID-19 mainly causes alveolar edema with hemorrhage, bronchiolitis, alveolitis, and pulmonary interstitial fibrosis [2]. With the gradual understanding of the disease, CT is reserved for hospitalized, symptomatic patients for assessing the progression course of COVID-19 [3][4][5][6]. Recent studies have used semi-quantitative methods to observe the lung changes during COVID-19 from the onset of symptoms to recovery with CT images [7,8].…”
Section: Introductionmentioning
confidence: 99%